The effectiveness of fish feeding behaviour in mirroring trawling-induced patterns. (October 2017) - Mangano, M.C.; Bottari, T.; Caridi, F.; Porporato, E.M.D.; Rinelli, P.; Spanò, N.; Johnson, M.; Sarà, G.
Abstract: The ability to observe and predict trawling-induced patterns at spatial and temporal scales that are relevant to inform realistic management strategies is a challenge which scientists have consistently faced in recent decades. Here, we use fish feeding behaviour, a biological trait easily impaired by trawling disturbance, to depict alterations in fish condition ( i.e. individual fitness) and feeding opportunities. The benthivorous fish Mullus barbatus barbatus was selected as a model species. The observed trends of responses to trawling in prey species confirmed the effectiveness of a non-trawled zone in sustaining higher levels of diet diversity ( e.g. quantity and quality of ingested prey) and fish condition values ( e.g. morphometric and physiological Condition Index). Changes observed in fish prey selection confirmed the role of trawling disturbance in modifying the local soft bottoms community, producing alterations of prey availability that trigger shifts in fish diet. Trawling-induced feeding patterns, mirrored through stomach contents, can positively or negatively affect fish condition, the main driver of population dynamics in maintaining carrying capacity levels. Due to the widespread socio-economic value of the red mullet fishery, and the current exploitation status, evidence gathered by the proposed bottom-up trait based approach might inform future trawling adaptation strategies, and tailor spatial conservation measures supporting an Ecosystem-Based Fisheries Management. Graphical abstract: Highlights: Fish feeding behaviour depict alterations in fish condition and feeding opportunities. A bottom-up trait based approach to inform the next trawling management strategies. Protected benthic communities provide beneficial effect on red mullet growth and diet.